Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Imuruk Volcanic Field, Alaska - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates five data subsets of the Imuruk volcanic field on the northern Seward Peninsula, Alaska, covering approximately 80 km². All images were collected on 10 July 2021.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; Lava Field; MACS; Orthoimagery; Permafrost; point clouds; Seward Peninsula; Structure-from-Motion